Diversity of Antifungal Compounds-Producing Bacillus spp. Isolated from Rhizosphere of Soybean Plant Based on ARDRA and 16S rRNA - ARIS TRI WAHYUDI; BRAMANTYO JATI PRASOJO; NISA RACHMANIA MUBARIK (HAYATI Journal of Biosciences, 2010)
Plant growth promoting rhizobacteria (PGPR) play an important role in improvement of seed germination, root development, and water utilization by plants. These rhizobacteria can stimulate plant growth directly by producing growth hormones or indirectly by producing antifungal compounds/antibiotics to suppress phytopathogenic fungi. The objective of this research was to analyze the diversity of 22 antifungal-producing rhizobacteria of Bacillus sp. isolated from rhizosphere of soybean plant based on Amplified rDNA Restriction Analysis (ARDRA) and 16S rRNA Sequence. Restriction enzymes in ARDRA analysis, HinfI, HaeIII, and RsaI were used to digest 22 16S rDNA amplified from Bacillus sp. genomes. Based on this analysis, genetic diversity of 22 Bacillus sp. producing antifungal compounds were classified into eight different groups. Moreover, six selected isolates randomly from each ARDRA group that have strong activity to suppress fungal growth were analyzed for their 16S rDNA sequences compared with reference strains. The distributions of these isolates were genetically diverse on several species of Bacillus sp. such as B. subtilis, B. cereus, and B. fusiformis. ARDRA is a reliable technique to analyze genetic diversity of Bacillus sp. community in the rhizosphere.